Creativity and entrepeneurship atitudes of students from National University of Engineering and their relationship with some sociodemographic variables - Loli Pineda, Alejandro (2010)
The objective of this study is to know about the creativity and entrepreneurship attitude of the National Engineering University students, and their relationship with demographic and social variables taken from a sample of 202 students between the first and tenth semester. The analysis of the results shows that most of the students have a positive attitude towards the creativity and entrepreneurship. In that sense, the correlation between the creativity and their entrepreneurship components indicates a meaningful and positive association. There is a meaningful difference between the demographic and social variables and their relationship to the entrepreneurship levels (low, normal, and high) according to year of study. Among these variables are found the following: work experience, the idea to start a new business and the necessity of financial assistance, in other words, the presence of these variables let us to infer the perception differences in the creativity and entrepreneurship levels.